2022
DOI: 10.3389/feduc.2022.883443
|View full text |Cite
|
Sign up to set email alerts
|

What Makes an Excellent Teacher? Insights From Junior High School Students With a History of Disruptive Behavior

Abstract: Evidence of the powerful relationship between what teachers do and how effectively their students learn has led to reforms aimed at improving the quality of teaching. Most jurisdictions are now paying increased attention both to the initial and ongoing education of teachers, as well as methods to assess, reward and improve quality teaching. Predominant among these methods are frameworks that define observable elements of pedagogical practice for which there is evidence of benefit for student learning, engageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Overwhelmingly, the literature ( n = 9) posits that classroom teachers feel ill-equipped to manage the diverse needs of children with diagnosed conditions, developmental delay, psychopathology, socio-emotional behavioural conditions, and atypical development including sensory, communicative, physical, adaptive, cognitive, and motor domains. The implications for children who arrive at school with significant developmental delays and mental and physical health disabilities are that teachers and school-based social workers are ill-equipped to meet their specific needs in the mainstream classroom [ 26 ]. In the study conducted by Simpson et al [ 43 ] it was found that the intersection that exists between the discernment of disability and the features of abuse and neglect is complex, interferes with assessment outcomes, and requires highly skilled practitioners to have effective communication skills to determine what is impacting on the child.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Overwhelmingly, the literature ( n = 9) posits that classroom teachers feel ill-equipped to manage the diverse needs of children with diagnosed conditions, developmental delay, psychopathology, socio-emotional behavioural conditions, and atypical development including sensory, communicative, physical, adaptive, cognitive, and motor domains. The implications for children who arrive at school with significant developmental delays and mental and physical health disabilities are that teachers and school-based social workers are ill-equipped to meet their specific needs in the mainstream classroom [ 26 ]. In the study conducted by Simpson et al [ 43 ] it was found that the intersection that exists between the discernment of disability and the features of abuse and neglect is complex, interferes with assessment outcomes, and requires highly skilled practitioners to have effective communication skills to determine what is impacting on the child.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies [ 26 , 40 ] discussed the high degree of quality teaching practice required to cater to the emotional, social, and behavioural needs of students with high-incidence disabilities, such as ADHD, learning disorders, and autism, as the majority of these students are educated in a mainstream classroom where integration is the norm, and an absence of genuine inclusion is apparent [ 49 ]. Graham et al [ 26 ] highlighted the relational approach being assumed by a teacher aide to support students to experience inclusion as opposed to integration. A student’s social and emotional needs are more likely to be addressed when a close connection and trusting relationship can exist in the classroom with a key adult [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations